The impact of bio-silicic acid (BioSilAc) to increase productivity and water use efficiency in sugarcane - Sari, Indah Puspita; Kalbuadi, Donny Nugroho; Arisandy, Poppy; Mahali, Yusuf; Al Hamda, Habiburrahman Malik; Goenadi, Didiek Hadjar (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2025)
Sugarcane (Saccharum officinarum L.) is a vital plantation crop, serving as a raw material for various industries, including sugar, bioethanol, amino acids, and food ingredients. Therefore, the advancement of technologies aimed at increasing productivity and fertilization efficiency in sugarcane cultivation has become a priority. Bio-silicic acid (BioSilAc) is a technology that can optimize the cultivation process. This study evaluated the effectiveness of water and fertilizer usage in plant cane (PC) and ratoon cane (RC) during low rainfall by applying BioSilAc and its impact on sugarcane productivity. This research utilized a randomized block design with three treatments (P1: 100% NPK; P2: 100% NPK + BioSilAc; and P3: 75% NPK + BioSilAc) replicated three times. Observed variables included soil and leaf nutrient levels, sugarcane growth, and productivity. Daily and potential water consumption was measured in real-time using a sap flow meter to calculate water use efficiency for P1 (control) and P2, representing the BioSilAc application. The P3 treatment (75% NPK + BioSilAc) demonstrated the highest effectiveness in terms of fertilization efficiency and productivity, resulting in notable increases in crop yield and crystal sugar. The PC category saw increases of 13.5% and 12.4%, while the RC category experienced gains of 22.82% and 25.81%, respectively. Furthermore, water use efficiency was recorded at 22.55% for the PC category and 13.72% for the RC category. Our findings suggest that the application of BioSilAc not only increase the productivity of sugarcane but also improves both fertilizer and water use efficiency.